THE THICKNESS OF STORYTELLING: …making sense of Capitalocene from the Global South - Mascali, Gianluca; Insani, Tia Dianing; Joana Moreno Rivera, Selma; Ndlovu, Thuli (PIXO - Revista de Arquitetura, Cidade e Contemporaneidade, 2026)
This article proposes storytelling as a critical method for perceiving, communicating, and understanding the Capitalocene in urban territories of the Global South. Drawing from a workshop held in Berlin with researchers from Latin America, Africa, and Asia, the work brings together situated stories and visual provocations, weaving a collective understanding of how capitalist urban experiences are lived and narrated across different contexts. More than representing experience, narrative and montage operate here as methodological, political, and epistemic devices—modes of inquiry that reveal how ways of dwelling, remembering, and resisting are shaped by capitalist logics in contemporary cities. In the face of fragmentation, exclusion, and socio-ecological crisis, the article affirms storytelling as a situated technology of knowledge—a collective, political, and counter-hegemonic gesture of world-building in the Global South.